Gambaran Kualitas Hidup pada Lansia Pengguna Gigi Tiruan Lepasan - Lutfia Rachma, Nindya; Ayu Ratih Utari Mayun, I Gusti (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: The aging process is a natural occurrence affecting individuals, influenced by various factors such as gender, employment, education level, and oral health. Tooth loss is a common consequence of aging. Removable dentures offer an alternative to rehabilitate missing teeth, replacing one or more teeth and surrounding tissues to restore function and prevent further damage. The objective of prosthodontic treatment for the elderly is to replace missing teeth with functional ones that enhance appearance, speech, and most importantly, chewing abilities. The ultimate goal is to help the elderly consume more nutrients. Objective: This study aims to assess the quality of life among senior citizens using removable dentures at the Ciracas nursing home in East Jakarta. Methods: A cross-sectional design and descriptive observational research methodology were employed. Seventy-one senior respondents aged 60 and above, using removable dentures at the Ciracas Nursing Home, participated in the study. The Oral Health Impact Profile 14 (OHIP 14) questionnaire was used for data collection. Results: Analysis revealed that 26 respondents (36.6%) reported good quality of life, 40 respondents (56.3%) reported moderate quality of life, and 5 respondents (7%) reported low quality of life. Conclusion: The quality of life of elderly residents of the Nursing Home in the Ciracas District of East Jakarta who wear removable dentures is categorized as moderate.